To explore the impact of augmented reality digital picture books in environmental education courses on environmental attitudes and environmental behaviors of children from different cultures - Chen, Shih-Yeh (Frontiers in Psychology, 2022)
Environmental education has long been closely related to sustainable development. In this study, in response to the United Nations Sustainable Development Goals (SDGs), an augmented reality digital picture book was created using the unique natural ecosystem of Taiwan's Orchid Island as a source of self-efficacy for science learning. Interactive environmental education learning through augmented reality drawing was used to determine whether students' science learning self-efficacy and environmental attitudes significantly influenced the environmental behavioral skills of culturally diverse children. In this study, 26 elementary 6th grade Taiwanese students and 26 elementary 6th grade Japanese students were invited to participate in an extended reality drawing activity as an environmental education curriculum. Based on the sample size of 52, the survey results were accurate within a sampling error of 3.8% with a confidence level of 95%. A questionnaire survey was administered to the 52 students after the event. After the valid questionnaire samples were collected, a partial least squares structural equation modeling (PLS-SEM) analysis was conducted with Smart PLS 3.0 on the small sample. The results of the study showed that students who had a better self-efficacy in science learning were more likely to engage in conservation actions related to the natural environment in their daily lives. In this study, the constructs of environmental behavior were further discussed and the hypothesis model was validated using the quantitative empirical method. The results of the study revealed good reliability, convergent validity, and discriminant validity of the constructs in the hypothesis model, and the hypothesis model itself was validated. In the validated model, students' science learning self-efficacy affects the sustainability of their environmental behaviors, but only through the role of environmental attitudes. However, the environmental attitudes construct plays a fully mediating role in the model.